O desenvolvimento de capacidades dinâmicas de cidades inteligentes - Welter, Clarice Vepo do Nascimento (2024)
The nature of dynamic capabilities and their impact on the development of smart cities are not widely discussed in the literature. However, with the growing interest of scholars in the phenomenon of smart cities, the role that dynamic capabilities play in the development of these cities has become a relevant topic in academia. However, there is still a lack of discussion on how the development of these dynamic capabilities occurs in a smart city. Therefore, analyzing the development of the dynamic capabilities of smart cities, from the lens of microfoundations, and their relationship with urban intelligence seems to be timely and necessary. To achieve this research objective, a single case study was developed in Florianópolis, considered the smartest city in Brazil according to the Connected Smart Cities Ranking (2023). This study, of a descriptive and exploratory nature, used a qualitative approach, involving different actors of the quadruple helix (Government, Universities, Companies and Civil Society Organizations). Data collection included interviews conducted during the month of July 2023, analysis of documents such as reports and the municipality's Master Plan, as well as images and videos from the social networks of the actors involved. Data analysis was carried out through content analysis, following the phases proposed by Bardin (2014): pre-analysis, exploration of the material and treatment of results, inference and interpretation. The results showed that Florianópolis has initiatives in all dimensions proposed by Giffinger et al. (2007), with emphasis on the dimensions of smart economy, smart people and smart life. The investigation of the microfoundations of dynamic capabilities revealed a series of key processes, routines and skills present in the urban environment of Florianópolis, which enabled the development of its intelligence. These microfoundations constitute an essential outline for the development of the dynamic capabilities of smart cities and directly influence the scope of urban intelligence. The research demonstrated empirically that the capabilities of 'sense', 'seize', 'align' and 'transform' are related to the dimensions of a smart city, contributing to its intelligence. These capabilities are operationalized by several microfoundations, composed of processes, routines, and practices that have enabled Florianópolis to develop initiatives and solutions in all dimensions of a smart city. A wide range of factors perceived as prerequisites for the development of smart cities were highlighted, highlighting the city's innovation ecosystem, multi-stakeholder partnerships, and a government open to dialogue. The theoretical contribution of this study lies in the refinement of the theory of dynamic capabilities, particularly relevant in dynamic urban environments. The research advances the literature by identifying and operationalizing the microfoundations of each dynamic capability, highlighting the importance of continuous monitoring of the population's needs and expectations. In addition, the thesis proposes three microfoundations for the capability to 'align', advancing the literature on smart cities. In the managerial field, the thesis offers a dynamic perspective on how cities can gain and sustain a competitive advantage, providing a framework of dynamic capabilities that support urban transformation. It also suggests that understanding these capabilities should be an integral part of the curriculum of public managers, contributing to the sustainable and inclusive development of cities, aligned with the objectives of the 2030 Agenda, specifically objective 11.